Tutupan Terumbu Karang di Perairan Pulau Larearea Kabupaten Sinjai Sulawesi Selatan - Ridha Alamsyah; Armita Permatasari; Irfan Fauzi (Gorontalo Fisheries Journal, 2019)
The condition of coral reefs in Indonesia continues to experience pressure due to human activities and global warming. This study aims to determine the coral coverage in the waters of Larearea Island which will be the basis in the management and conservation of coral reef ecosystems in Sinjai Regency. Measurements were made at each observation station using the Line Intercept Transect method. Standardization of categorizing coral reef conditions refers to the Decree of the Minister of Environment No. 04/ MENLH / 02/2001 concerning the standard criteria for Coral Damage. The results obtained, coral cover in the waters of Larearea Island are included in the broken to moderat category. Live corals are dominated by massive and branched growth types, while dead corals are dominated by dead coral with algae.